A study of the effect of new cobalt (II) complex and cyclophosphamide drug on (GPT, ALP) activity by using in vivo system - Baghdad Science Journal (مجلة بغداد للعلوم)
The present work involved a study the effect of cobalt(II) complex with formula [CoL(H2O)NO3] .4ETOH where L=Nitro [5-(P-nitro phenyl) -4-phenyl-1,2,4 traizole-3-dithiocarbamato hydrazide] aqua. (4) Ethanol and anti-cancer drug - cyclophosphamide on specific activity of two liver enzymes (GPT,ALP) by utilizing an in vivo system in female mice. On the enzymatic level an inhibition in the activity of GPT was noticed in different body organs such as liver, kidney and lung. The inhibition was noticed in both test and cyclophosphamide drug (cp). Mice were treated with three doses of cyclophosphamide (90,180, 250) ?g/ mouse for three days. The same doses were used for the cobalt (II) complex. The liver shows the highest rate of(GPT) inhibition compared to other organs. The ratio was about 90% at three doses of cobalt (II) complex, this ratio was similar to ratio inhibition of cyclophosphamide at the same doses. On the contrary the enzyme ALP showed high activation in different organs such as liver, kidney and lung in both groups, test and cyclophosphamide drug (cp) at the three doses (90, 180, 250) ?g /mouse. The result showed the highest ratio of activation in the kidney comparable with other organs. The maximum activation of cobalt(II) complex was about 1198% at a concentration 180µg/mouse.There are significant differences(P